Profitabilitas, Likuiditas dan Leverage Pengaruhnya terhadap Nilai Perusahaan dengan Kebijakan Dividen sebagai Variabel Moderasi - Saeful Fachri; Rahmat Taufik; Rival Aldiano; Intan Pandini (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze profitability, liquidity and leverage on firm value and examine role of dividend policy as a moderating variable in this interaction. Based on Signaling and Pecking Order Theories, profitability is measure through Return on Assets (ROA), liquidity through Current Ratio (CR), leverage through Debt to Equity Ratio, firm value through Price to Book Value (PBV) and dividend policy through Dividend Payout Ratio. A quantitative approach was used with a population of 47 companies listed on the Jakarta Islamic Index (JII) during the 2019-2023 period, resulting in 65 observation samples. Data analysis used Moderated Regression Analysis (MRA) and multiple linear regression to test the hypothesis. The results show that ROA has a positive and significant effect on PBV, indicating profit efficiency that increases investor confidence in accordance with signaling theory. CR does not have a significant positive effect on PBV in line with pecking order theory which prioritizes internal financing. DAR has a significant positive effect on PBV indicating the effective use of debt for expansion in accordance with pecking order theory. The interaction between ROA and DPR is not significant on PBV indicating that dividend policy is less effective as a signal in this context. DPR significantly as a signal in this context. DPR significantly moderates the effect of CR on PBV confirming dividends as a signal of financial stability. The interaction between DAR and DPR is not significant on PBV indicating that other factors such as profitability are more dominant in investor assessment.